Étude comparative relative à l’assurance de dommages entre le nouveau Code civil du Québec et le Code civil actuel - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1992)
The author briefly compares the new Civil Code of Québec with the one currently in force. While the new Civil Code retains some of the features of the present legislation, such as case law, over the last decade, new provisions and updated language in particular have resulted in substantial differences. This study illustrates the traditional and new approaches in three specific areas: rules of insurance, rules of interpretation and civil liability.